If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 9 + 8x + -7 = 3x + 12 + -1 Reorder the terms: 9 + -7 + 7x + 8x = 3x + 12 + -1 Combine like terms: 9 + -7 = 2 2 + 7x + 8x = 3x + 12 + -1 Combine like terms: 7x + 8x = 15x 2 + 15x = 3x + 12 + -1 Reorder the terms: 2 + 15x = 12 + -1 + 3x Combine like terms: 12 + -1 = 11 2 + 15x = 11 + 3x Solving 2 + 15x = 11 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 2 + 15x + -3x = 11 + 3x + -3x Combine like terms: 15x + -3x = 12x 2 + 12x = 11 + 3x + -3x Combine like terms: 3x + -3x = 0 2 + 12x = 11 + 0 2 + 12x = 11 Add '-2' to each side of the equation. 2 + -2 + 12x = 11 + -2 Combine like terms: 2 + -2 = 0 0 + 12x = 11 + -2 12x = 11 + -2 Combine like terms: 11 + -2 = 9 12x = 9 Divide each side by '12'. x = 0.75 Simplifying x = 0.75
| -8+x=27 | | x-.40x=9.66 | | 3(x-10)=51 | | 3-7x=6x-127 | | 0.9-(200/x^2)=0 | | 4/3-6 | | -29(a+3)-a=0 | | -24=4+10v+4v | | (6t^2-3t+2)-(-6t^2+3t-5)=0 | | 9n-(4m-8)=53 | | 7s+14=6s+15 | | .833=.75x | | 3/5=y+1/9 | | (4/9)n+6=4/3 | | 3x-8=11x-32 | | -21+3b=-11b+7 | | 9(2x+1)=3x-7x | | 4-7x=6x+9 | | 96x-12=12x-4 | | 13y=4(3y-5) | | 11=x/5-3 | | 12x+2y=1139.30 | | 18y-18y=8 | | x(.5)+.5=5.5 | | -6x+10+3x=4 | | 1(6x+1)=3(9-x) | | 4w-13w=54 | | 2x^2-540=0 | | c-8/-2=11-4c/11 | | 3x=4(5x+2) | | -24=6x+3x+3 | | 3x+y+z=37 |